Model of organization, control and quality of service communication in research process - Brambilla Barrueto, Carmen Elizabeth (2014)
This research is based on the problem of communication observed in the Academic Office of Research of the UCV: Universidad César Vallejo Campus Chiclayo (AOR-UCVCH), facing such a situation, it was suggested hypothetically that a proposal of organization and control model, focusing on a manual of procedures which overcomes such problem. For this purpose, it was worked with a population composed of 1 820 registered students in the 16 professional schools at Universidad César Vallejo Campus Chiclayo, taking a sample of 406 students from 1st to 10th period of studies. The student’s ages oscillate between 16 and 29 years; to which it was applied a questionnaire to collect information about communication process that occurs at AORUCV- CH, serving as a diagnostic on quality of service that is offered and thus to formulate the proposal. Theoretical information was added to the questionnaire, using specific theories related to the variables of study obtaining the theoretical foundations to design the theoretical organization and control model, focusing on a manual of procedures, which application should be centered on the fundamental values practices and an assessment. Therefore, it was possible the acquisition of a fundamental tool to be handed over the AOR-UCV-CH advising its application prior to co-ordinations and approvals from correspondent levels; this manual will supervise that UCV-CH students and responsible teachers of the main curricular experiences, and also all employees and university community, improving the quality of service in communication, fundamental aspect of the work of specifically administrative nature.